2011
DOI: 10.2215/cjn.04150511
|View full text |Cite
|
Sign up to set email alerts
|

Attending Rounds

Abstract: SummaryHypokalemic paralysis represents a medical emergency requiring both rapid diagnosis and treatment. In this Attending Rounds a patient with hypokalemia and metabolic acidosis is presented to emphasize the role of routine laboratory studies in the assessment of such patients so that a correct diagnosis can be made and appropriate treatment can be initiated promptly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…Some authors suggest that steroid therapy should be considered in these patients as the presence of severe dRTA causing hypokalemic paralysis reflects the severity of the underlying autoimmune tubulointerstitial nephritis (3,(5)(6)(7)(8). As an example, Soy et al reported a primary Sjögren syndrome patient with dRTA who presented with symptoms of HPP.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that steroid therapy should be considered in these patients as the presence of severe dRTA causing hypokalemic paralysis reflects the severity of the underlying autoimmune tubulointerstitial nephritis (3,(5)(6)(7)(8). As an example, Soy et al reported a primary Sjögren syndrome patient with dRTA who presented with symptoms of HPP.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical spectrum of renal tubular acidosis may be silent to life-threatening 4. In Sjogren's syndrome, severe symptomatic hypokalemia with periodic paralysis and respiratory arrest has been reported in only a few cases 8 9. Potassium deficiency can induce muscle ischaemia and, in case of severe depletion, muscle necrosis and rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the possible pathogenic role of anti-CAII antibodies, mice injected with human CAII develop antibodies to this protein and develop a syndrome similar to Sjögren syndrome with lymphocytic and plasma cell infiltration in the salivary glands and kidneys along with a urinary acidification defect (42). However, it is not clear that immunosuppressive therapy improves the RTA associated with Sjögren syndrome (43).…”
Section: Question 2amentioning
confidence: 99%